A Study to Identify Socio-Demographic and Lifestyle Risk Factors Associated with Type 2 Diabetes Mellitus and Hypertension - Sampat Raj Nagar; Manish Jain; Shalabh Sharma (Medsci Publications, 2016)
Introduction: Hypertension and diabetes mellitus are chronic non- communicable diseases of increasing importance. Estimating risk factors of hypertension and diabetes is very crucial as this forms the basis for planning of prevention of these disorders. Objective: conducted to identify socio-demographic and lifestyle risk factors associated with Type 2 Diabetes Mellitus and Hypertension. Material and method: An OPD based case-control study was conducted in RNT Medical College & attached hospitals, Udaipur from July 2014 to December 2014. Cases and controls were selected, examined and interviewed using semi- structured, pre-tested questionnaire containing questions regarding the socio demographic data and lifestyle risk factors. Results: Maximum hypertensive cases (43.3%) were in age group 50-59 years. The prevalence of hypertension and diabetes were observed more in SES class I, individuals with positive family history and sedentary life style. Observed proportion of smokers was 34.3% in HTN cases and 38.8% in type 2 diabetes cases. Observed proportion of HTN cases was 62.5% among high salt users. Conclusion: Continuous efforts need to be made for identifying and developing simple tools to forecast the risk of developing HTN and DM II among different age group, gender and ethnic groups.